The Race for Global Superpower Status: Is the U.S. Losing Its Grip? - Raupp, Brian; Maniam, Balasundram; Houston State University, Sam (International Journal of Engineering and Technology, 2018)
Following World War II, the United States emerged as a true global superpower, a position it continues to hold today. However, as every superpower throughout history, the United States has, and continues to encounter nations looking to challenge its position as the global leader. This paper explores and analyzes other nations or regions which are potential candidates to disrupt American hegemony. Factors in determining a countryâ€™s candidacy will include economic power, military power, government stability, the size of territory and quality of life. These factors will be compared to those of the United States to identify challengers to the current American position. Ultimately, this paper will explore whether the United Statesâ€™ position as the lone global superpower is in jeopardy and by whom.Â